2023
DOI: 10.1038/s41586-022-05611-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous behaviour is structured by reinforcement without explicit reward

Abstract: Spontaneous animal behaviour is built from action modules that are concatenated by the brain into sequences1,2. However, the neural mechanisms that guide the composition of naturalistic, self-motivated behaviour remain unknown. Here we show that dopamine systematically fluctuates in the dorsolateral striatum (DLS) as mice spontaneously express sub-second behavioural modules, despite the absence of task structure, sensory cues or exogenous reward. Photometric recordings and calibrated closed-loop optogenetic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 88 publications
1
67
3
Order By: Relevance
“…In agreement with this, a recent study showed that spontaneous open-field behavior (without explicit reward) can be clustered into discrete sub-second behavioral modules (“syllables”), and that behavioral modules with bigger striatal dopamine transients are more likely to reoccur in the future. Furthermore, pairing optogenetic stimulation of dopaminergic neurons with specific behavioral modules reinforces subsequent use of those specific modules—an effect that was detectable even during a subsequent, nonstimulated session ( 46 ). Our present results complement this study by also showing the converse: Pairing-reduced dopaminergic signaling with a specific task—akin to eliciting a specific behavioral module—reduces future performance of the same specific task.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, a recent study showed that spontaneous open-field behavior (without explicit reward) can be clustered into discrete sub-second behavioral modules (“syllables”), and that behavioral modules with bigger striatal dopamine transients are more likely to reoccur in the future. Furthermore, pairing optogenetic stimulation of dopaminergic neurons with specific behavioral modules reinforces subsequent use of those specific modules—an effect that was detectable even during a subsequent, nonstimulated session ( 46 ). Our present results complement this study by also showing the converse: Pairing-reduced dopaminergic signaling with a specific task—akin to eliciting a specific behavioral module—reduces future performance of the same specific task.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently used depth MoSeq to show that the levels of the neuromodulator dopamine fluctuate within the dorsolateral striatum (DLS) during spontaneous behavior, and that these fluctuations are temporally aligned to syllable transitions 15 : On average, dopamine levels rise rapidly at the onset of each syllable, and then decline toward the end of the syllable. Furthermore, the average magnitude of dopamine fluctuations varies across syllables.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 The validity of the rapid signals has already been substantiated through comparisons to FSCV 9 and enables extensive studies of behaviorally related, fast neurochemical changes. 26,30 A thorough validation and comparison to established methods designed to monitor neurotransmission over longer periods must also be performed.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recently, a new methodological paradigm has been opened by genetically encoded biosensors in combination with optical imaging technologies. When combined, these have potential to capture rapid dynamics over extended periods of time and an expanding palette of tools and techniques now allow for advances, such as multichannel recordings and depth resolution. , The validity of the rapid signals has already been substantiated through comparisons to FSCV and enables extensive studies of behaviorally related, fast neurochemical changes. , A thorough validation and comparison to established methods designed to monitor neurotransmission over longer periods must also be performed.…”
Section: Discussionmentioning
confidence: 99%